Mengimplementasikan Prinsip Penuntun Sekolah Dalam Menejemen Perubahan - Setiawan, Ahmad Bagas; Prabowo, Galuh (Pondok Pesantren As-salafiyah Asy-syafi'iyyah, 2024)
Education is one means of maintaining the survival of a nation. Quality education produces people who have superior skills and abilities who are able to advance the country. To achieve a goal, implementation is very important. Everyone needs to put their thinking into practice to achieve their goals. Change scan be handled and the legitimacy and function of the organization guaranteed by incorporating this information. Formal education in schools seeks to create unique human beings by encouraging the intellectual growth of students, thereby increasing the general level of intelligence in the country. The aim of this article is to change and provide principles for every teacher to educate students so that students grow more and can know their direction during the learning process. This research uses a qualitative method with a narrative design, this method is used to create a picture or describe the implementation of school guiding principles in managing change for students. to collect detailed actual information that describes existing symptoms, identifies existing problems or looks at prevailing conditions and practices. from the results of this research is that teachers To be able to treat children appropriately and help them develop better behavior in the future, teachers must be aware of their initial abilities. Teachers must be able to encourage students to be able to think critically and creatively. the relationship between students' critical thinking and cognitive development. Teachers must adapt learning methods to the different characters of each child and their different abilities. Education can build a person's character and personality to be better in life and relationships as a member of society